2020
DOI: 10.3390/polym12040823
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Novel Syntheses of a Series of Unique Hybrid PLGA-Chitosan Polymers for Potential Therapeutic Delivery Applications

Abstract: Discovering new materials to aid in the therapeutic delivery of drugs is in high demand. PLGA, a FDA approved polymer, is well known in the literature to form films or nanoparticles that can load, protect, and deliver drug molecules; however, its incompatibility with certain drugs (due to hydrophilicity or charge repulsion interactions) limits its use. Combining PLGA or other polymers such as polycaprolactone with other safe and positively-charged molecules, such as chitosan, has been sought after to make hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…This indicated that neither drastic alterations of materials occurred until the 30 th day, nor secondary products were formed. Specific IR maxima identified in Figure 5 were attributed to both PLGA and Ibuprofen as follows: asymmetric and symmetric stretching of –CH 3 and –CH 2 (between ~3000 and ~2850 cm −1 ), C=O symmetric stretching (between ~1760 and ~1690 cm −1 ), overlapped –OH bending and –CH 3 symmetric deformation (~1385 cm −1 ) [ 68 , 69 ]. Vibrations corresponding to LA (methyl’s asymmetric deformation) and GA (methylene’s symmetric deformation) were identified at ~1450 cm −1 , while characteristic vibrations of C–O–C moiety from both units were evidenced between ~1170 and ~1080 cm −1 [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that neither drastic alterations of materials occurred until the 30 th day, nor secondary products were formed. Specific IR maxima identified in Figure 5 were attributed to both PLGA and Ibuprofen as follows: asymmetric and symmetric stretching of –CH 3 and –CH 2 (between ~3000 and ~2850 cm −1 ), C=O symmetric stretching (between ~1760 and ~1690 cm −1 ), overlapped –OH bending and –CH 3 symmetric deformation (~1385 cm −1 ) [ 68 , 69 ]. Vibrations corresponding to LA (methyl’s asymmetric deformation) and GA (methylene’s symmetric deformation) were identified at ~1450 cm −1 , while characteristic vibrations of C–O–C moiety from both units were evidenced between ~1170 and ~1080 cm −1 [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chitosan coating architecture is influenced by the method of preparation, the type of chitosan, and the molecular properties of the nanoparticle´s materials; thus, the choice of the correct mechanism will lead to better results. Notably, the covalent mechanisms produce more stable interactions easily characterizable by analytical techniques such as infrared, nuclear magnetic resonance, or HPLC [52][53][54]. However, the procedure can become complicated, hardly scalable, and challenging to reproduce.…”
Section: Decoration Of Nanoparticles With Chitosan: Methods and Mechamentioning
confidence: 99%
“…Notably, the covalent mechanisms produce more stable interactions easily characterizable by analytical techniques such as infrared, nuclear magnetic resonance, or HPLC [ 52 , 53 , 54 ]. However, the procedure can become complicated, hardly scalable, and challenging to reproduce.…”
Section: Decoration Of Nanoparticles With Chitosan: Methods and Mementioning
confidence: 99%
“…Hybrid polymers can result from the total or part combination of natural and synthetic polymers. As is the case of the combination of the PLGA (synthetic polymer) and the CS (natural polymer) that result in the PLGA-CS hybrid polymer that has been studied in several areas, namely in therapeutic delivery [ 19 ]. The choice of polymers for the formation of scaffolds, based on their characteristics, has proved to be crucial in the properties and applicability of the final scaffold.…”
Section: Polymers Natural/syntheticmentioning
confidence: 99%